1976
DOI: 10.1182/blood.v48.4.491.491
|View full text |Cite
|
Sign up to set email alerts
|

Establishment of erythropoiesis following bone marrow transplantation in a patient with congenital hypoplastic anemia (Diamond-Blackfan syndrome)

Abstract: Marrow transplantation was attempted in a 13-yr-old boy with congenital hypoplastic anemia who had never responded to corticosteroid therapy. Prior to the transplant, he had received 238 transfusions, at least 12 of which were from his father. He was prepared for grafting with antilymphocyte globulin, procarbazine, and total body irradiation (1000 rads). The patient, whose red cells were Group B, then received marrow cells from his Group O, histocompatible, sister. Thereafter, reticulocytes, Group O erythrocyt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
19
0
2

Year Published

1981
1981
2015
2015

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 62 publications
(21 citation statements)
references
References 13 publications
0
19
0
2
Order By: Relevance
“…Steroid‐intolerant or transfusion‐dependent patients may be considered for haematopoietic stem cell transplantation (HSCT), which is the only definitive treatment for the haematological manifestations of DBA. The first HSCT for DBA was reported in 1976 confirming DBA as a transplantable disease (August et al , ). After this initial case, several authors reported successful transplantations in DBA patients (Iriondo et al , ; Wiktor‐Jedrzejczak et al , ; Lenarsky et al , ; Gluckman et al , , ; Zintl et al , ; Mori et al , ; Greinix et al , ; Saunders et al , ; Lee et al , ; Mugishima et al , ; Wagner et al , ; Bonno et al , ; Ladenstein et al , ; Morimoto et al , ; Vettenranta & Saarinen, ; Willig et al , ).…”
mentioning
confidence: 99%
“…Steroid‐intolerant or transfusion‐dependent patients may be considered for haematopoietic stem cell transplantation (HSCT), which is the only definitive treatment for the haematological manifestations of DBA. The first HSCT for DBA was reported in 1976 confirming DBA as a transplantable disease (August et al , ). After this initial case, several authors reported successful transplantations in DBA patients (Iriondo et al , ; Wiktor‐Jedrzejczak et al , ; Lenarsky et al , ; Gluckman et al , , ; Zintl et al , ; Mori et al , ; Greinix et al , ; Saunders et al , ; Lee et al , ; Mugishima et al , ; Wagner et al , ; Bonno et al , ; Ladenstein et al , ; Morimoto et al , ; Vettenranta & Saarinen, ; Willig et al , ).…”
mentioning
confidence: 99%
“…High-dose corticosteroid therapy, androgens, and/or erythropoietin have been used with limited success in refractory patients. Previous reports on the HSCT for DBA patients indicated that HLAidentical sibling donor BMT led to the favorable outcomes compared with alternate donor BMT (8)(9)(10)(11)(12)(13)(14)(15)(16)(17). Most recipients were unresponsive to PSL and were extensively transfused until the transplantation.…”
mentioning
confidence: 99%
“…This is important for prospective clinical trials and bone marrow transplants. Transplants have had variable success (August et al, 1976;Greinix et al, 1993;Iriondo et al, 1984;Wiktor-Jedzrejczak et al, 1987). Intrinsic humoral inhibitory processes in the marrow microenvironment would make successful transplantation difficult.…”
Section: Discussionmentioning
confidence: 99%